Design, synthesis, anticancer evaluation and molecular docking of new V600EBRAF inhibitors derived from pyridopyrazinone - Amin, Kamelia Mahmoud; El-Badry, Ossama Metwally; Rahman, Doaa Ezzat Abdel; Ammar, Usama Magdi; Abdalla, Mohamed Mostafa (European Journal of Chemistry, 2016)
Design and synthesis of some new pyridopyrazinone derivatives as anti-proliferative agents is described. The cytotoxic activities of the synthesized compounds against melanoma cell line (LOXIMVI), ovarian cell line (OVCAR3), thyroid cell lines (CAL62, FTC133, BCPAP and ML1) and colon cell lines (HT29 and HCT116) were investigated. Results revealed that most compounds were active and compound 3d was the most active one. It exhibited promising activity against all tested cell lines. In addition, in vitro kinase assay against both WTBRAF and V600EBRAF was performed for all synthesized compounds. Furthermore, molecular docking of tested compounds was established with active site of V600EBRAF kinase domain. Results of kinase inhibition assay and molecular docking revealed that, compounds 1, 3d, e, h, i, 5d, e and 6b were potent inhibitors for V600EBRAF kinase enzyme involved in number of cancer types as melanoma, ovarian and thyroid cancer. The newly synthesized pyridopyrazinones substituted with different substituents at C-3 or fused with triazine heterocycle at C-3 and C-4 afforded potent V600EBRAF inhibitors and exhibited promising cytotoxic activities against different cancer types such as melanoma, ovarian, thyroid and colon cancer.